Self-Report and Administrative Data on Disability and IEP Status: Examining Differences and Impacts on Intervention Outcomes. (March 2023) - Shogren, Karrie A.; Pace, Jesse R.; Wittenburg, David C.; Raley, Sheida K.; Hicks, Tyler A.; Rifenbark, Graham G.; Lane, Kathleen Lynne; Anderson, Mark H.
Differences in perceptions of disability between students and administrators can play a role in youth's educational experience. This study used data from a cluster randomized controlled trial (C-RCT) of the Self-Determined Learning Model of Instruction (SDLMI) to first compare student self-report of disability status to matched administrative data and second to examine the impact of the data source utilized on trial outcomes. The findings demonstrate substantive gaps between self-reports and administrative reports of disability. While some differences might be expected, the size of the differences is notable, especially given that many students identified as having an Individualized Education Program in administrative data did not self-identify as receiving services or having a disability. The findings advance understanding of discrepancies in self-reported disability and administrative data in secondary intervention research. We also found the interpretation of group differences (students with vs. without disabilities) on trial outcomes was sensitive to the source of the data (self vs. administrative) used to establish disability status. This finding can inform future research and policy, as the data source selected to define disability populations across research studies likely has substantive impacts on conclusions drawn about the impact of interventions on students with disabilities. We cannot identify all the factors driving these differences. Nonetheless, the findings underscore the importance of providing clarity about decisions made in defining disability populations in intervention research.